Understanding the experiences of Mandarin-speaking patients diagnosed with life-threatening cancer in Australia. Issue 5 (October 2015) - Chiang, Yung-Chih; Collins, Anna; Chopra, Prem; Lu, Ti; Tan, Eng-Seong; Couper, Jeremy W.
Abstract: Objective: People from ethnic minority groups who receive cancer care outside their country of origin may experience poor survival and psychological outcomes relative to that nation's majority groups. This exploratory qualitative study aimed to understand the experience of a large minority group of Mandarin-speaking cancer patients (MSCPs) after diagnosis and treatment of their cancer in Australia, with a view to delineate if cultural or linguistic factors affected the quality of care provided. Method: We employed an exploratory qualitative design involving interviews with 22 MSCPs who were treated during 2009 at the Peter MacCallum Cancer Centre (PMCC) in Melbourne, Australia. Participants were interviewed by a bilingual psychiatrist, audiotaped, transcribed in Mandarin, and then translated into English before being subjected to thematic analysis by two independent researchers. Results: MSCPs experienced notable challenges as a result of both language difficulties and differing cultural approaches, which often limited their understanding of their disease and impeded their ability to access quality care and adequate support. The results call for Australia and other Western nations with increasingly diverse populations to consider how cancer care can be modified to better support people from minority groups to effectively cope with their diagnosis and treatment. Significance of results: This study raises several suggestions for service improvement, including the development of bilingual communication aids, improved educational opportunities for clinical staff to aid their mastery of cultural issues and effective interpreter consultations, and improved access to supportive services offering culturally specific strategies.